Sign Language Interpreter or Facilitator?: An Experience in the Chilean Educational Context - Perez Toledo, Vanessa; Munoz Vilugrón, Karina; Chávez, Karina Jazmín (Íkala, Revista de Lenguaje y Cultura, 2020)
The inclusion of Deaf students in regular classrooms has highlighted the need for the Chilean Sign Language Interpreter to act as a mediator between two languages: The sign language and oral language. Therefore, the objective of this study is to analyze the training and functions of the Chilean Sign Language Interpreter in the educational context. The instrument to achieve the objective was a semistructured interview with 12 Sign Language interpreters and 3 key informants in this field. The results show the informality in the training process, a series of prescribed functions, which distance themselves significantly from the non-prescribed ones, and a series of barriers that the educational context establishes for the interpretation. From these, the figure of the Chilean sign language facilitator emerges to help respond to the needs for access to learning by Deaf students in educational contexts.